The Effect of Credit Collection Policy on Loan Performance in the Banking Sector in Central region of Uganda - Alex Semusu; Eton Marus; Kaaya Siraje; Eliab Byamukama Mpora (Husnayain Business Review, 2026)
This study examined the effect of credit collection policy on loan performance in the banking sector of Central Uganda. Despite the presence of formal credit collection frameworks, commercial banks in Uganda continue to experience persistent loan defaults, raising concerns about the effectiveness of existing collection practices in improving loan performance. Anchored in a pragmatic research paradigm, the study adopted a mixed-methods approach. Quantitative data were collected using structured questionnaires administered to selected commercial banks and analyzed through Covariance-Based Structural Equation Modeling (CB-SEM) using Jeffrey’s Amazing Statistical Program (JASP) version 0.19.3.0. Exploratory Factor Analysis (EFA) was employed to validate the measurement model. Qualitative data were obtained through key informant interviews and analyzed thematically to complement and explain the quantitative findings. The results revealed that credit collection policy had a negative but statistically non-significant relationship with loan performance (β ≈ −0.04, p > 0.05). While the measurement model demonstrated acceptable construct validity and reliability, the structural model indicated that formal credit collection policies did not significantly influence loan performance outcomes. Qualitative findings provided further insight, showing that collection practices were largely reactive, with recovery efforts typically initiated only after loans became non-performing. In addition, heavy reliance on third-party debt collectors and delayed borrower engagement weakened internal ownership and accountability in the credit recovery process. The study contributes empirical evidence from Uganda’s banking sector by demonstrating that the effectiveness of credit collection policy is determined less by formal policy design and more by proactive implementation and early borrower engagement. By integrating quantitative SEM results with qualitative insights, the study offers a nuanced explanation for the weak linkage between credit collection policies and loan performance, with implications for strengthening credit risk management policies in developing economies.